2022
DOI: 10.38007/dps.2022.030408
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Distributed Based on PLC Software Redundancy

Abstract: At present, with the development of technology, dynamic distributed system (DDS) have been widely developed in many fields, and the maintenance requirements of the system have also undergone great changes. There are still many places worth discussing about the redundant fault-tolerant mechanism for data loss., so this paper studies the DDS based on PCL soft redundancy. The research on DDS in this paper can be divided into three parts. First, it introduces the architecture of distributed system(DS), dynamic mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[7] Next, the study area is clipped using the vector polygon of the Dasigou River Basin (initial section) as a mask. [8] Then, using ENVI software, ROIs (Region of Interest) for various land use types are established to extract the land use information for the years 2002, 2009, 2015, and 2020 using supervised classification methods. [9] Finally, a comparative analysis is conducted on the results of the supervised classification to obtain the temporal sequence of land use changes in the study area, as shown in Figure 2 and Table 1.…”
Section: Climate Characteristicsmentioning
confidence: 99%
“…[7] Next, the study area is clipped using the vector polygon of the Dasigou River Basin (initial section) as a mask. [8] Then, using ENVI software, ROIs (Region of Interest) for various land use types are established to extract the land use information for the years 2002, 2009, 2015, and 2020 using supervised classification methods. [9] Finally, a comparative analysis is conducted on the results of the supervised classification to obtain the temporal sequence of land use changes in the study area, as shown in Figure 2 and Table 1.…”
Section: Climate Characteristicsmentioning
confidence: 99%